Chloride diffusion and binding in concrete containing NO2 sequestered recycled concrete aggregates (NRCAs). (12th July 2021) - Ariyachandra, Erandi; Peethamparan, Sulapha; Patel, Shrish; Orlov, Alexander
Highlights: Effect of NRCAs on chloride diffusion and binding in new OPC concrete. NRCAs synthesized from 2 and 20-year-old demolished concrete. NRCAs reduced the chloride penetrability in concrete compared to conventional RCAs. NRCAs increased the chloride binding capacity compared to conventional RCAs. Chloride binding mechanism in NRCA incorporated concrete. Abstract: This study investigates the effect of NO2 sequestered recycled concrete aggregates (NRCA) on chloride ion diffusion and chloride binding capacity of concrete. Two types of NRCAs were used as a partial replacement for natural fine aggregate in fresh OPC mixtures at 20% and 40% replacement levels by volume. Control mixtures with conventional recycled concrete aggregates (RCA) were also evaluated for comparison purposes. The water-permeable porosity, rapid chloride permeability, long-term chloride diffusivity, and chloride binding capacity of the test concrete mixtures were evaluated. Results showed that the presence of NRCA reduced porosity as well as both short-term and long-term chloride ion permeability compared to conventional RCA containing concrete. Most importantly, the addition of NRCAs enhanced the chloride binding capacity of concrete. Thermogravimetric and X-ray diffraction analyses demonstrated increased formation of Friedel's and Kuzel's salts in concrete due to the incorporation of NRCA. Based on the test results, a mechanism is proposed for the enhanced chloride resistance in NRCA incorporated concrete.